Rights beyond borders : the global community and the struggle over human rights in China - Foot, Rosemary, 1948- (Oxford University Press, 2000)
Over the five decades since the establishment of the United Nations Charter and Universal Declaration of Human Rights, issues of human rights have become a dominant feature of our global community. An acceptance has grown of the treatment of individuals and groups within domestic societies as a legitimate focus of global attention. Played out dramatically in the US media, China has received a huge amount of this global attention, with many democracies sustaining a human rights element in their policies towards China. This book examines the affect that this normative evolution has had on the behavior of individuals, states, institutions, and advocacy networks, and assesses its impact on the relations between key international players and China. Focusing on the period since the Tiananmen bloodshed in June 1989, Rosemary Foot examines China's international and internal responses to the global attention paid to their human rights record. Foot expertly uncovers the conditions under which international human rights norms influence behavior, and determines how norms operate in the global system.